PERMETHRIN SELECTION ON THE ADULTS OF ANOPHELES STEPHENSI FROM SOUTH OR IRAN - H.Ladonni (Tehran University of Medical Sciences, 1993)
A wild strain of Anopheles stephensi Liston (BAN-PR), originating from Bandar-Abbas, south of Iran, was submitted to selection with permethin at the adult stage. Ten successive generations of permethrin selection on the adults resulted in only 2.2 fold increase in tolerance. Crossing experiments on the selected and unselected strains indicated that the gene/genes for observed tolerance is inherited as an intermediate character with no indication of sex linkage. Synergist test on the selected strain indicated ~t oxidative detoxification might be the major mechanism in the selected in for the observed tolerance. The relationship between resistance to dieldrjn and malathion in perrnethnn selected strain was studied. The resalt indicated that there might he a positive correlation between resistance to dieldrin, malathion and permethrin in An.stephenesi from Bandar-abbas.